Análise paramétrica das abóbadas gaussianas de Eladio Dieste - Melachos, Felipe Corres (2020)
This research has as its object of study the discontinuous gaussian vaults, the dominant variation of the gaussian vault structural typology, designed and built by the Uruguayan engineer Eladio Dieste. The gaussian vaults are doubly-curved rigid structural surfaces resulting from Dieste’s constructive explorations with reinforced brickwork. Furthermore, the geographical and chronological scope of this academic endeavor matches the construction time and location of Dieste’s gaussian vaults: between 1955 and 2000 in the territories of Uruguay, Brazil, Argentina and Spain. The research framework arises from the ostracism of Eladio Dieste’s legacy in academic publications in a historical and a constructive perspective, which is highly contrasting with his contributions in the fields of architectural and engineering structural design through extensive reinforced-brick shells explorations. However, this ostracism is a collateral damage of the Eurocentric approach present in Modern Architecture bibliography during the twentieth century, and paradoxical to the resurgence of academic and constructive explorations of doubly curved rigid structural surfaces in the first decades of the 21st century. The main objective within this research is to verify and identify the existence of underlying geometrical relationships within the body of Dieste`s work designed and structured as discontinuous gaussian vaults. However, the analysis of the geometry itself was initially conducted by means of redrawing and the parametric modelling of Dieste’s Gaussian Vaults from the original drawings. The implementation of the aforementioned methodological procedures was fostered by the year spent in the Università degli Studi di Ferrara for the PDSE-CAPES scholarship grant. When it comes to the expected contributions from this investigation, it is important to mention a deepening of the understanding of the relationship amongst Dieste`s shell form and constructive processes, as well as insights regarding his gaussian vaults` design process.